2012
DOI: 10.1136/bjophthalmol-2012-301907
|View full text |Cite
|
Sign up to set email alerts
|

Human papillomavirus: a predictor of better survival in ocular surface squamous neoplasia patients

Abstract: Background Although human papillomavirus (HPV) has been implicated in the pathogenesis of ocular surface squamous neoplasia (OSSN), no study has so far dealt with the prognostic role of HPV. In this study the presence and significance of HPV in OSSN and its correlation with p16INK4a immunoexpression was determined. Methods HPV was detected by HPV-L1 capsid genespecific multiplex PCR using PGMY09/11 primers, and genotyping was done by linear array on 64 OSSN patients and 15 conjunctival controls. p16INK4a immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
1
3

Year Published

2012
2012
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 29 publications
1
24
1
3
Order By: Relevance
“…Human papillomavirus and human immunodeficiency virus have also been cited as possible cofactors in OSSN that may influence the prognosis. 3,[18][19][20] Recurrence developed in 17% of 48 patients herein with follow-up data, which is similar to that in other studies (17%-41%). 1,7 Larger tumors (2 cm) and those with a diffuse growth pattern had a higher risk of recurrence.…”
Section: Correlation Of Clinicopathological Features With Recurrence-supporting
confidence: 80%
“…Human papillomavirus and human immunodeficiency virus have also been cited as possible cofactors in OSSN that may influence the prognosis. 3,[18][19][20] Recurrence developed in 17% of 48 patients herein with follow-up data, which is similar to that in other studies (17%-41%). 1,7 Larger tumors (2 cm) and those with a diffuse growth pattern had a higher risk of recurrence.…”
Section: Correlation Of Clinicopathological Features With Recurrence-supporting
confidence: 80%
“…In human pathology the prevalence of HPV in ocular surface disease varies dramatically, according to variations in the assays used to detect the virus, as well as geography and genetic susceptibility (Woods et al 2013), and the utility of p16INK4a immunoexpression for predicting HPV in ocular surface squamous neoplasia was evaluated but, unlike cervical cancers, it seems that there is no correlation. In fact, the overexpression of p16INK4a in OSSN was significantly associated with HPV (Chauhan et al 2012), while Auw-Haedrich et al (2008) have reported HPV and p16INK4a positivity in conjunctival intraepithelial neoplasias (CIN) but they did not observe any association between p16INK4a and HPV.…”
Section: Discussionmentioning
confidence: 99%
“…Ocular surface squamous neoplasia, that is conjunctival squamous neoplasia, is a highly intersting tumour which is evaluated by Scott et al [2002], Biswas et al [2010], Aktas et al [2012], Chauhan et al [2012], Di Girolamo [2012 as well as by Kao et al [2012].…”
Section: Discussionmentioning
confidence: 99%
“…In a material of 64 cases of OSSN, HPV infection was detected in 11% -it also indicated a better prognosis [Chauhan et al 2012]. …”
Section: On Hpv Prevalence In Ocular Lesiomentioning
confidence: 99%